PENGARUH DUKUNGAN SELEBRITI, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HIJAB RABANNI (Studipada Mahasiswi Fakultas Ekonomika dan Bisnis Univesitas Stikubank Semarang) - Mona NoviaNeamy, 10.05.51.0113 (Students Journal of Economic and Management, 2017)
This study aimed to analyze the influence of celebrity endorsements, brand image and product quality on purchasing decisions hijab Rabanni the students of the Faculty of Economics and Business Unisbank Semarang. The population in this study were students of the Faculty of Economics and Business Unisbank Semarang who buy and use Rabanni hijab. The minimum sample size in this study, the number of research indicators as much as 20 so that the number of samples is 5 times the number of indicators or as many as 5 x 20 = 100. The sampling technique uses accidental sampling. The analysis tool used is the test of validity, reliability, multiple linear regression. The results of the analysis can be concluded that: Support celebrities positive influence on purchase decisions. Brand image positive influence on purchase decisions. The product quality has positive influence on purchasing decisions Keywords: celebrity endorsements, brand image, product quality and purchasing decisions